The theme of the mystery of power in the thought of N.A. Berdyaev: A Literary and Philosophical Study - Usachev, Aleksandr V (2021)
The purpose of this article is to raise the question of power and its essence again in the context of how Russian religious philosophy, in this case, N. A. Berdyaev, sees it. The methodology of this work is taken from the program works on the history of Russian philosophy by V. V. Zenkovsky and N. O. Lossky, and consists in creating a comparative basis for comparing the main concepts of power in Western philosophy and Russian philosophy. Even a rough analysis shows that the government eludes discourse and eschews rational definitions, otherwise it would be possible to explain the revolution in Russia by its fundamental character.The material of the article can be used in social and anthropological studies of power, which increases and extends its influence even to the simplest relationships but rather than reducing it. The creators of new eras always face a new kind of responsibility in the sense that they are responsible to the living generations for how they use power and whether it is for good or for harm.